Des trésors personnels - Élise Marcia (In Situ)
In Arles, the costume of the Arlésienne, the traditional dress of the women of Arles, is an emblem of the city and its region. The women who wear this costume restore, preserve and wear items that are often very old. They are faced with a cruel paradox: choosing to wear the dress can only accelerate its gradual destruction and prevent it from being handed on to future generations. Exploring the wardrobes of the Arlésiennes, it is possible to understand the itinerary of some of these ‘treasures’ and to see something of the links that bind them to their present owner. In order to describe their costume, the women of Arles put forward several values, at the same level: their historic value, that is the knowledge of the trajectory of the object seen as bearing witness to the past; the relational value, which corresponds to the object carrying traces of a relationship with the ancestors and former owners of the costume; and personal values, the object evoking the tastes, the itinerary and the qualities of the woman of Arles who owns it today. By taking an interest in the narratives that surround these costumes from Arles we obtain a glimpse of the tensions that underpin the conservation of this special garment, and the fact of wearing it. In order for the dress to remain ‘alive’ and ‘authentic’, the owner must draw on registers that are at one and the same time personal, familial and regional.